On the probability of route existence in mobile wireless networks. (6th March 2007) - Lee, Muhammad Hisyam; Salleh, Shaharuddin; Sanugi, Bahrom; Olariu, Stephan
This paper presents a route selection method in mobile wireless networks to a given destination based on the probability that the route is still available for a packet to be sent. The probability is based on the knowledge at each node of the geographic position of all the other nodes in the network and taking into account the mobility of the nodes and the dependencies between links in a computed route. We derive a simple closed form expression for the computation of the availability of a route, which can then be used to select the best route.